2020
DOI: 10.2147/ott.s254514
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Value of the Preoperative Plasma D-Dimer Levels in Patients with Upper Tract Urothelial Carcinoma in a Retrospective Cohort Study</p>

Abstract: Elevated plasma D-dimer levels were thought to be associated with decreasing survival in various cancers. The relationship between plasma D-dimer levels and clinicopathology and the optimal D-dimer cutoff as a prognostic predictor has not been determined in patients with upper tract urothelial carcinoma (UTUC). We aimed to investigate the prognostic value of preoperative plasma D-dimer levels as a predictor of patient outcomes in UTUC following radical nephroureterectomy. Patients and Methods: We retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Chen et al reported that according to their Retrospective Cohort Study data, elevated plasma D-dimer levels predicted an increased risk of cancer recurrence and a worse prognosis in patients diagnosed with Upper Tract Urothelial Carcinoma, which is a rare urinary tumor with an unfavorable prognosis [ 19 ]. Their data found that plasma D-dimer levels ≥ 0.36 mg/L correlated with higher pathological T stage, tumor grade, and invasion of cancer to the blood vessels or lymphatics.…”
Section: Reviewmentioning
confidence: 99%
“…Chen et al reported that according to their Retrospective Cohort Study data, elevated plasma D-dimer levels predicted an increased risk of cancer recurrence and a worse prognosis in patients diagnosed with Upper Tract Urothelial Carcinoma, which is a rare urinary tumor with an unfavorable prognosis [ 19 ]. Their data found that plasma D-dimer levels ≥ 0.36 mg/L correlated with higher pathological T stage, tumor grade, and invasion of cancer to the blood vessels or lymphatics.…”
Section: Reviewmentioning
confidence: 99%
“…Patients with lower D-dimer levels may have inactive tumors and smaller tumor volumes. Elevated plasma D-dimer levels predict an increased risk of tumor recurrence and a poorer prognosis, according to data from a retrospective cohort analysis of patients with epithelial carcinoma of the upper urinary tract by Chen et al D-dimer levels have been shown to be useful in assessing the treatment and prognosis of a wide variety of malignancies 35 , including colorectal and uroepithelial malignancies 11,35 , as well as gastric 9,19,36 , lung 37 , breast 7,25 , cervical cancers 23 , and high-grade musculoskeletal sarcoma 38 .…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that pre-operative D-dimer levels can help in improving the risk stratification and a more accurate prediction of recurrence and survival. This can help in decision making for follow-up scheduling, administration of adjuvant therapies, and precise individualized treatment for patients [ 26 ]. In another study on prognostic value of preoperative inflammation-based predictors in patients with bladder carcinoma by Gui et al, they reported that high plasma fibrinogen levels are associated with a more aggressive clinical stage and plasma fibrinogen levels may be used to predict survival outcome of patients with bladder carcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%